Development of Clause Chaining in Korean - Choi, Soonja (Frontiers in Psychology, 2020)
Korean is a language with the verb at the end of a clause/sentence. In chaining several clauses (each consisting of a subject and a verb) in a sentence, a conjunction (e.g., -ko 'and then', -ese 'by means of’) is suffixed to the verb of a non-final clause. Korean has an extensive set of conjunctions that connect to the next clause, expressing temporal, causal, and contrastive relations among others. In this paper, I lay out a developmental trajectory of clause chaining construction in Korean based on longitudinal and cross-sectional data samples, focusing on conjunctive forms and functions as well as morphological and syntactic properties of connected clauses in a sentence. The database comes from longitudinal naturalistic speech data of five children collected regularly over different time periods between two and five years of age, and from elicited descriptions of short video events from children − aged 3, 4, 6, 8 and 10 years − and adults. The results show that, at least from two years of age, the Korean children in the sample start connecting clauses using appropriate conjunctions. Within six months, they acquire several major conjunctions that express temporal, causal, conditional, and contrastive relations between events. By four years of age, the children’s clause chains are quite adult-like in terms of the repertoire of conjunctive forms and functions, and of the morphological and syntactic features of the clauses that connect to the main clause. In particular they learn to express temporal relations that have some disjuncture between events. However, four-year-olds still lack the ability to appropriately refer to differential subjects of the chained clauses and also to connect multiple clauses in a sentence. The elicitation data reveal that further development in clause chaining occurs over several years - with a milestone at 10 years - and through adulthood, particularly in relation to appropriate referential marking, conjunction frequency, and segmentation of a macro event into sub-events for clause-chaining construction. These developmental processes are presented from a cognitive perspective, in particular with regard to concept of temporal relation, reference specification involving two or more entities, and perceptual saliency of event type.